Pelaksanaan E-Budgeting Dalam Penyusunan Program Kerja Organisasi Perangkat Daerah Pada Pemerintah Kota Surabaya - Wike Putri, Gusti Ayu; Priyanto (Soetomo Magister Ilmu Administrasi, 2024)
This study aims to know the excussion , achievement of the e-Budgeting output in the preparation of the work program of regional apparatus organizations in the City of Surabaya, along with the weakness of e-Budgetting system. This research is a type of qualitative research with a descriptive approach, using the theory of budgeting according to Munandar (2015: 18 ) and guidelines for achieving the output of implementing e-Budgeting in the preparation of work programs for regional apparatus organizations in the Surabaya City government, based on the Decree of the Mayor of Surabaya Number: 188.45/237/436.1.2. / 2019 Regarding the Standard of Regional Spending Unit Prices for the City of Surabaya for the 2020 Fiscal Year. The data collection for this research was carried out through observation, interviews, document studies. Furthermore, the data analysis used is data reduction, data presentation, and drawing conclusions The results of the study found that the analysis of the implementation of e-Budgeting in the preparation of work programs was carried out through steps, namely data collection, data processing to prepare the desired budget, preparing temporary budgets, discussing temporary budgets that had been prepared, compiling definitive budgets, collecting data for evaluation as well as processing and analyzing these data to draw conclusions The output achievement of implementing the e-Budgeting system is that the activity budget output is real and already describes the achievement of the OPD-OPD activity targets directly, the Details of Output (RO) of the OPD-OPD work program budget are very specific and reflect the tasks and functions of the OPD-OPD that produce them , . the Output Detail (RO) unit is the same as the KRO unit (Output Detail Classification), Output Details (RO) in the preparation of the work program budget are not transparent so that the Surabaya City Government and OPD-OPD cannot compile and change the RO nomenclature independently because to changing the output details must go through discussions with the TAPD or the Regional Government Budget Team. The weaknesses of the e-Budgeting system, namely changes in policies that apply to some, the use of several satellite applications that have not been integrated with the e-Budgeting system and massive data loading, then the solution to these weaknesses is a ) the need to always ensure that adjustments to the exception algorithm b) do not affect the basic e-Budgeting algorithm, b) the need for uniformity in the satellite application format so that it is standardized with the budgeting format to facilitate the integration process c) the need to continue upgrading infrastructure both in terms of hardware and software to support the process occurred in the e-budgeting application, the development of the e-Budgeting 2.0 application was also carried out. The researcher recommends that BPKAD Surabaya should a) always ensure that the adjustment of the exception algorithm does not affect the basic e-budgeting algorithm, always ensure that the exception algorithm adjustment does not affect the basic e-budgeting algorithm, b) standardize the satellite application format so that it is standardized with the e-budgeting format for facilitating the integration process, c) continuing to upgrade the infrastructure both in hardware and software to support the processes that occur in the e-Budgeting application as well as developing the eBudgeting 2.0 application